The Degree of Commitment of States Parties in Responding to the Requests for Cooperation from the International Criminal Court: Jordan as a Case Study - Ta’ani, Dyala; Zuqaibah , Ahmad (Dirasat: Shari'a and Law Sciences, 2021)
This research focuses on adherence of member states to the requests for cooperation from International Criminal Court and the forms of such commitment. It also shows the legal implications of not adhereing to these requests by stating the legal responsibility of member states in the court and the extent of their obedience to its statute and the degree of referring to the Assembly of States Parties and the Security Council. The study focuced on Jordan as a member of the court’s statute when it refused to extradite former Sudanese President Omar al-Bashir and the reasons behind refusing to cooperate with the court. This indicates the insufficient number of guarantees necessary to respond and implement court decisions, including requests for cooperation, and therefore, it is necessary to amend the provisions of the court system in order to achieve the goal of its existence. The descriptive and analytical approach was used in this research. The study reached the following conclusions: the court is considered a multilateral international organization, that the cooperation of the parties with the court constitutes one of the guarantees surrounding the mandatory force of its decisions and that the lack of cooperation of the states parties with the court constitutes a major obstacle to the exercise of its jurisdiction. In addition, the Security Council is considered one of the guarantees for the implementation of the decisions of the International Criminal Court. Also, the court lacks some organs that should be subordinate to it and work according to its system and instructions.